Control of high blood pressure by Acupuncture In subjects with essential hypertension - Abbas, Hazim k.; Ja’afar, Isra’a F.; Saeed, Basil N. (Journal of the Faculty of Medicine Baghdad, 2012)
advancing age. The risk of cardiovascular disease in adults is lowest with systolic BP